The Representation of Social Discrimination in Zootopia 2 (2025) Movie - Vidya Kartika Dewi; Masnia Rahayu (Universitas Islam Negeri Palopo, 2026)
This study examines the representation of social discrimination in Zootopia 2 (2025), focusing on how inequality, prejudice, and marginalization are portrayed through selected dialogues, scenes, and visual symbols. The film was chosen because it presents discrimination through an animated narrative that remains relevant to contemporary issues of stereotyping, exclusion, and unequal power relations. Using a qualitative descriptive method, this research applies Stuart Hall’s Representation Theory and Alan Swingewood’s Sociology of Literature to analyze how discrimination is constructed and represented in the film. Unlike previous studies that mainly discuss discrimination in animated films as interpersonal prejudice, this study examines discrimination as a structural and historical process shaped by ideological control, historical erasure, and social exclusion. The findings reveal that reptiles, particularly through the character of Gary De’Snake, are represented as marginalized subjects whose identities are shaped by dominant narratives and collective prejudice. Therefore, Zootopia 2 functions as a cultural text that not only reflects social inequality but also critiques how power and representation sustain discrimination in society.